What Is the Role of Firm-Specific Pay Policies on the Gender Earnings Gap in Canada? - Jiang Li; Benoit Dostie; Gaëlle Simard-Duplain (Institute of Labor Economics (IZA), 2020)
Using data from the Canadian Employer-Employee Dynamics Database between 2001 and 2015, we examine the impact of firms' hiring and pay-setting policies on the gender earnings gap in Canada. Consistent with the existing literature and following Card, Cardoso, and Kline (2016), we find that firm-specific premiums explain nearly one quarter of the 26.8% average earnings gap between female and male workers. On average, firms' hiring practices – due to difference in the relative proportion of women hired at high-wage firms, or sorting – and pay-setting policies – due to differences in pay by gender within similar firms – each explain about one half of this firm effect. The compositional difference between the two channels varies substantially over the life-cycle, by parental and marital status, and across provinces.
Keywords: J16; J31; J51; J71; 330; gender wage gap; firm effects; marital status; linked employer-employee data; pay-setting; sorting